Ellipsoid Zone Integrity and Visual Acuity Changes during Diabetic Macular Edema Therapy: A Longitudinal Study - Lucy J. Kessler; Gerd U. Auffarth; Dmitrii Bagautdinov; Ramin Khoramnia (Journal of Diabetes Research)
Purpose. Ellipsoid zone (EZ) integrity is identified as a potential biomarker for therapy surveillance and outcome prediction of visual acuity (VA). However, only a few studies report long-term results of over 1 year of clinical and anatomical changes in patients with diabetic macular edema (DME). This study is aimed at describing the long-term VA and anatomical outcomes in spectral domain optical coherence tomography (OCT) (relative ellipsoid zone reflectivity ratio, central macular thickness, and volume) in patients with DME treated with antivascular endothelial growth factor (anti-VEGF) therapy. Furthermore, we studied the correlation between EZ integrity and changes in visual acuity. Methods. 71 eyes of 71 patients were included in this retrospective study. Clinical characteristics were reviewed yearly. OCT data were assessed at baseline and after 1, 3, and 5 years. EZ parameters were quantified automatically. OCT parameters and visual outcome were correlated and analyzed in multivariable regression models. Results. EZ reflectivity ratio correlated with functional outcome in DME patients from baseline to fifth year at all time points (for all p<0.05). EZ reflectivity improved the most in the first year of treatment (0.68 to 0.75; p<0.05) and declined gradually until year 5 of therapy (0.71; compared to baseline p>0.05). Similarly, best VA was achieved after 1 year (0.40 logarithm of the minimum angle of resolution (logMAR) to 0.28 logMAR; p<0.001) and declined gradually until year 5. Final VA in year 5 was comparable to baseline (0.45 logMAR, compared to baseline p>0.05). Together with baseline VA, baseline EZ parameters did predict VA outcome after 1 year (p<0.05). Concordantly, VA and EZ parameters from year 1 were associated with VA outcome in year 2. Conclusion. This study described the long-term course of EZ changes during anti-VEGF treatment in DME patients. In addition, our results underlined the potential of EZ parameters as novel OCT biomarkers for prediction of VA outcomes during therapy.